(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2023)
Based on specimens deposited in the Fish Collection of Facultad de Ciencias (UDELAR), in this note we make the first records for three species of Rineloricaria (Siluriformes: Loricariidae) in Uruguay.